A bibliometric study for global hotspots and trends in animal-assisted interventions (1983–2023) - Feng, Xiaowei; Zhao, Shanguang; Zhang, Dong; Yi, Qing; Chen, Yanlan; Zhang, Xinding (Frontiers in Psychiatry, 2025)
BackgroundAs a therapeutic approach, Animal-Assisted Intervention (AAI) has gained increasing recognition for enhancing both psychological and physical health. However, bibliometric studies in this field remain scarce.MethodsThis study aims to analyze AAI-related research from 1983 to 2023 using bibliometric methods. It examines sources of literature, core journals, highly cited documents, country and institutional distribution, prolific authors, and high-frequency keywords while tracking the evolution of research themes in AAI. A thematic search using the Boolean operator “OR” and AAI-related keywords in the Web of Science database yielded 405 articles, and data mining and visualization of these results were performed.ResultsThe findings reveal a substantial increase in the number of published articles and citations over the past decade, indicating a rising research interest in this field. The United States and Purdue University have played a leading role in this area. Currently, AAI research is shifting from basic studies to intervention strategies targeting specific populations and diseases. Future research trends may include enhanced international collaboration, standardization of research methods, and the development of more targeted interventions.ConclusionThese findings provide researchers, funding agencies, and policymakers with scientific insights and recommendations for future research directions in AAI.